Nonlinear seismic response of arch dams considering joint opening effects and boundary conditions of discontinuous foundation - A. Ferdousi (Numerical Methods in Civil Engineering)
In most cases, concrete arch dams in the presence of suitable abutments, have high bearing capacity and more appropriate safety regarding the cost aspects, when compared to the other types of dams. However, according to the dam failure statistics, site specific conditions and abutment instability are the main factors of concrete dam’s failure. In this paper, the effects of two important factors on earthquake response of high arch dams are considered. These factors are: effects of contraction joints opening between the dam monoliths and appropriate rock foundation boundary conditions. Nonlinear seismic response of dam  reservoir foundation system includes dam-canyon interaction, dam body contraction joint opening, discontinuities (sliding planes) of foundation rock and failure of the jointed rock and concrete materials. Therefore, a finite element program for nonlinear dynamic analysis of 3D dam reservoir  foundation system was developed. Karun 4 Dam as a case study was analyzed and the results revealed the essential role of modeling discontinuities and boundary conditions of rock foundation under seismic excitation. Also, The results demonstrate that the contraction joint openings during strong earthquakes are substantial and greatly change the arch to cantilever stress distribution in the dam body.